2022
DOI: 10.3390/encyclopedia2020054
|View full text |Cite
|
Sign up to set email alerts
|

Formulation in Surfactant Systems: From-Winsor-to-HLDN

Abstract: Formulation is an ancient concept, although the word has been used only recently. The first formulations made our civilization advance by inventing bronze, steel, and gunpowder; then, it was used in medieval alchemy. When chemistry became a science and with the golden age of organic synthesis, the second formulation period began. This made it possible to create new chemical species and new combinations “à la carte.” However, the research and developments were still carried out by trial and error. Finally, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 415 publications
0
15
0
Order By: Relevance
“…When the CI is added, oil droplets are not created, which may indicate that the overall system is at the optimal HLD (equal to zero), with minimal emulsion stability (Figure ). Although the concentration of additives is not explicitly included as a variable in the general HLD equation, it has been shown that this is an important variable as well. For the DE in the crude oil–water system, the coalescence frequency is largest at 2 ppm of DE. Apparently, this concentration of the DE corresponds to the stability minimum regime, with the HLD at around zero (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…When the CI is added, oil droplets are not created, which may indicate that the overall system is at the optimal HLD (equal to zero), with minimal emulsion stability (Figure ). Although the concentration of additives is not explicitly included as a variable in the general HLD equation, it has been shown that this is an important variable as well. For the DE in the crude oil–water system, the coalescence frequency is largest at 2 ppm of DE. Apparently, this concentration of the DE corresponds to the stability minimum regime, with the HLD at around zero (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…For more details, see reviews by Salager and co-workers. [65][66][67]69 Another useful characteristic of a surfactant is the "packing parameter", also known as the "Israelachvili parameter". 72−76 The packing parameter, P, characterizes the most favorable micellar structure of a model surfactant in water (Figure 6).…”
Section: Approachesmentioning
confidence: 99%
“…More recently, the concept of HLB has been extended and refined via the introduction of the so-called HLD (hydrophilic–lipophilic difference) (Figure ). The HLD analysis takes into account not only the nature of the surfactant but also the nature of the oil itself.…”
Section: Data-driven and Semiphenomenological Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the surfactant or linker molecule allows a gradual polarity change at the vicinity of the interface (shell of the capsule), and thus more beneficial interactions between surfactant-aqueous phase and surfactantoil phase where solubilized EOs bioactive compounds are encountered (Chu et al, 2014;Salager et al, 2005Salager et al, , 2019. This allows the Winsor R relation (Bourrel & Schechter, 2010;Salager al., 2022;Winsor, 1954) to become R < 1 (i.e., hydrophiliclipophilic deviation, HLD N < 0) if an O/W emulsion is the target (Forgiarini et al, 2021;Salager et al, 2020). On the other hand, R = 1 or R slightly lower than 1, would be necessary if a bicontinuous microemulsion (HLD N = 0) or O/W microemulsion are needed, respectively (Ontiveros et al, 2013;Queste et al, 2007;Salager et al, 2020).…”
Section: Encapsulation Of Eosmentioning
confidence: 99%